Korelasi Status Vaksin dengan Kecemasan Keluarga Terkonfirmasi Covid 19 - Miko Eka Putri; Mila Triana Sari (Universitas Baiturrahim, 2023)
Covid-19 cases are still increasing, both in the world and in Indonesia. Based on data from the World Health Organization (WHO) in March 2021, the total number of confirmed cases in the world reached 122,992,844 positive cases. The updated number of deaths due to the COVID-19 pandemic in the world has reached 2,711,071 cases, and 397,950,709 have received the vaccine. This research is an analytic study with a cross-sectional design. The purpose of this study was to determine the correlation of vaccine status with family anxiety confirmed by covid 19 in Legok Village, Jambi City. The sampling technique was accidental sampling of 83 respondents. The analysis used is univariate and bivariate analysis with chi square and product moment . The results of the analysis that the role and being confirmed by covid were not related to anxiety due to covid 19 (0.81), but there was a significant relationship between vaccine status and family anxiety level (0.011). We would like to thank the Legok Village Head who has facilitated this research. It is hoped that the family and family members will get the next vaccine.